Dictionary of symbols - Liungman, Carl G., 1938- (Santa Barbara, Calif. : ABC-CLIO, 1991)
The functions, meanings, history, and systems of approximately 1,500 Western graphic symbols are illustrated. Includes the sign's history, meanings, and systems in which it is used.
Ideographic dictionary -- Word index -- Graphic index -- Graphic search index.
Translation of: Symboler.
Includes bibliographical references and indexes.
Wilson's Junior High School.
Wilson's Senior High School.
Adult
Keywords: Picture-writing -- Dictionaries; Signs and symbols -- Dictionaries; Picture-writing -- Dictionaries; Signs and symbols -- Dictionaries